2018
DOI: 10.5014/ajot.2018.030494
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Fall Prevention Interventions for Community-Dwelling Older Adults: A Systematic Review

Abstract: These findings can inform the delivery and integration of fall prevention interventions from acute care to community discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 82 publications
3
29
0
10
Order By: Relevance
“…The most recent Cochrane systematic review on the topic had already found 159 trials with 79,193 participants back in 2012 [ 10 ], and concluded that multiple component group exercise and home-based exercise as well as home safety interventions reduce rate of falls and risk of falling. This is in line with other systematic reviews and meta-analyses, which found multifactorial interventions including exercise to be most effective, with exercise as a single intervention showing significant effects as well [ 67 69 ]. However, another recent Cochrane review showed that the majority of these multifactorial and multiple component studies are of low quality with unclear or high risk of bias [ 70 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The most recent Cochrane systematic review on the topic had already found 159 trials with 79,193 participants back in 2012 [ 10 ], and concluded that multiple component group exercise and home-based exercise as well as home safety interventions reduce rate of falls and risk of falling. This is in line with other systematic reviews and meta-analyses, which found multifactorial interventions including exercise to be most effective, with exercise as a single intervention showing significant effects as well [ 67 69 ]. However, another recent Cochrane review showed that the majority of these multifactorial and multiple component studies are of low quality with unclear or high risk of bias [ 70 ].…”
Section: Discussionsupporting
confidence: 89%
“…Due to the high relevance and socioeconomic impact of falls in the older population, it is not surprising that numerous attempts based on various approaches have been made to reduce falls and fall-related consequences. The overall goal behind this is to optimize individual health trajectories in the aging process, which can be achieved by ensuring that community-dwelling older people receive high-quality, evidence-based fall prevention services [ 67 ]. Several systematic reviews and meta-analyses have been conducted in the field to identify best possible intervention measures, with somewhat diverse target groups and focusing on different intervention approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article provided an example of how to apply evidence from systematic reviews on productive aging to inform and guide clinical decision making (Berger et al, 2018;Elliott & Leland, 2018;Hunter & Kearney, 2018;Liu et al, 2018;Smallfield & Lucas Molitor, 2018a, 2018b. For further evidence-based information on productive aging, see the American Occupational Therapy Association's (AOTA's) Occupational Therapy Practice Guidelines for Productive…”
Section: Resultsmentioning
confidence: 99%
“…Occupational therapy practitioners can teach strategies and establish reminders to label food and exercise safe, proper storage practices. Self-feeding may be resolved educating on the use of adaptive equipment such as scoop bowl/plate, built up utensil handles, or a rocker knife [45]; and fall risk interventions may be tailored to address fall prevention in the kitchen and during food-related activities [46,47]. Occupational therapy practitioners can assess and treat eating and swallowing difficulties by addressing oral–motor skills, bolus management, or dysphagia [48].…”
Section: Interventions—occupationmentioning
confidence: 99%